Pengujian Ketidakpastian Pengukuran Alat Ukur Debit Air Rendah Biaya Berbasis Mikro Kontroler Arduino: A Low-Cost Water Discharge Measurement Tool Based on an Arduino Microcontroller for Testing Measurement Uncertainty - Dwijaya Febriansyah (Fakultas Teknik Universitas Pancasila, 2023)
Commercial water flow meter costs increase when utilized in low-cost installations like pico-hydro, small-scale process industries, irrigation, and other rural or non-commercial technology applications that require measurements of water discharge. Utilizing a low-budget flow meter equipped with a freely available microcontroller is the answer to this issue. In contrast to commercial measuring devices, this low-budget measuring instrument needs to be examined and verified ahead of time using other commercial measuring devices to establish the measurement's uncertainty value and make it feasible to use. By using the Arduino Uno microcontroller and the YF-DN40 turbine sensor, this low-budget flow meter is capable of producing <5% difference in discharge readings and <1% measurement uncertainty.